Born of fury - Kenyon, Sherrilyn, 1965- (Kenyon, Sherrilyn, 1965- League., 2014)
"The war is on...Counted among the fiercest Andarion warriors ever born, Hauk is one of the five founding members of the Sentella: an organization that has declared war on the League. They rule the Ichidian universe with an iron fist and terrify it with an army of well-trained assassins. Hauk's enemies are legion, but he fears nothing and no one. He will do whatever it takes to survive and protect his Sentella brethren. Sumi Antaxas is one of the best assassins the League has ever trained. In her world, failure is not an option and she has never met a target she couldn't execute. So when she's assigned Hauk, she believes it'll be a quick and easy mission.But nothing is ever as simple as it seems, and Hauk is far better skilled than any she's faced before."--